2022
DOI: 10.1111/jgh.15944
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antithrombotic drug use on delayed bleeding with esophageal endoscopic resection

Abstract: Background and Aim Whether antithrombotic drugs increase the risk of post‐esophageal endoscopic resection bleeding is unknown. This study examined the effect of antithrombotic drugs, aspirin, thienopyridine, direct oral anticoagulants (DOAC), and warfarin, on post‐esophageal endoscopic resection bleeding. Methods We enrolled 957 patients (1202 esophageal tumors) treated with endoscopic resection and classified them based on antithrombotic drug use as no use, aspirin, thienopyridine, DOAC, and warfarin. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…DB rates were 4.5 % in the aspirin-continued group and 2.9 % in the aspirin-discontinued group. However, in the group of individuals on direct oral anticoagulants, the DB rates were much higher at 13 % [20]. Hence the rate of DB in esophageal ER can 3 Jadad Quality assessment tool for randomized control trial included in this meta-analysis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…DB rates were 4.5 % in the aspirin-continued group and 2.9 % in the aspirin-discontinued group. However, in the group of individuals on direct oral anticoagulants, the DB rates were much higher at 13 % [20]. Hence the rate of DB in esophageal ER can 3 Jadad Quality assessment tool for randomized control trial included in this meta-analysis.…”
Section: Discussionmentioning
confidence: 98%
“…However, this can change considerably with periprocedure antithrombotic use or coexistent conditions such as severe liver disease. Horie et al evaluated the role of antithrombotic drug use on DB after ER of esophageal lesions 20 . They found that the post-ER bleeding rate was 0.3 % in the group without antithrombotic drug use, consistent with prior reported rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation